2021
DOI: 10.1021/jacs.1c08881
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reverse Intersystem Crossing Promoted by Triplet Exciton–Photon Coupling

Abstract: Polaritons are hybrid light−matter states formed via strong coupling between excitons and photons inside a microcavity, leading to upper and lower polariton (LP) bands splitting from the exciton. The LP has been applied to reduce the energy barrier of the reverse intersystem crossing (rISC) process from T 1 , harvesting triplet energy for fluorescence through thermally activated delayed fluorescence. The spin−orbit coupling between T 1 and the excitonic part of the LP was considered as the origin for such an r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…The proposed concept is implicitly supported by several previous experimental studies. [45][46][47] Note that the concept of the cavity-free QED-ET reaction is fundamentally different from that of polariton chemistry [7][8][9][10][11][12][13][14][15][16][17][18][19][20] because it accounts for the effect of infinite one-photon states in the absence of strong light-matter interactions. Second, we established a unified theory to describe both radiative and nonradiative ET.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed concept is implicitly supported by several previous experimental studies. [45][46][47] Note that the concept of the cavity-free QED-ET reaction is fundamentally different from that of polariton chemistry [7][8][9][10][11][12][13][14][15][16][17][18][19][20] because it accounts for the effect of infinite one-photon states in the absence of strong light-matter interactions. Second, we established a unified theory to describe both radiative and nonradiative ET.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, several experiments demonstrated that QED effects can significantly affect chemical reactions under vibrational strong coupling, [7][8] which goes beyond the scope of traditional chemistry, providing new insights into fundamental science and promoting the development of cavity chemistry (polariton chemistry). [7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, to achieve vibrational strong coupling, specific dielectric environments are required, such as optical cavities or plasmonic cavities, leading to the difficulty of realizing cavity-modified chemical reactions. [21][22][23] Motivated by the recent development of cavity chemistry, we questioned whether it is possible to harness QED effects to control chemical reactions in the absence of cavities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, caution should be exerted in the use of these gradients, if the photon field strength or electron-photon coupling g is scaled by p N for a set of N parallel-oriented noninteracting photochromes or by p N/3 for a set of N randomly-oriented photochromes. 65 It is convenient to illustrate this by extending the CIS-JC model to a set of N parallel-oriented non-interacting identical-geometry photochromes. The resultant Tavis-Cummings-type model 25,67 (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, caution should be exerted in the use of these gradients, if the photon field strength λ or electron-photon coupling g is scaled by √ N for a set of N parallel-oriented noninteracting photochromes or by N/3 for a set of N randomly-oriented photochromes. 65 It is convenient to illustrate this by extending the CIS-JC model to a set of N parallel-oriented non-interacting identical-geometry photochromes. The resultant Tavis-Cummings-type model 25,67 (i.e.…”
Section: Discussionmentioning
confidence: 99%